Evaluating Insurance Funds as A Financing Source for Infrastructure Development: A Case Study of Indonesia - Berawi, Mohammed Ali; Dikun, Suyono; Bintoro, Ristu; Sari, Mustika; Susilowati, Suci Indah (CSID Journal of Infrastructure Development, 2023)
There is a funding deficit that cannot be covered by relying solely on government money to build Indonesia’s Infrastructure; consequently, additional sources of financing are engaging the private sector to fill the gap. Insurance funds are an alternative funding source in many countries, although their application is still at an early stage. By assessing the risks faced by insurance companies involved in infrastructure investment, this paper attempts to evaluate the use of insurance money as an alternative funding source for infrastructure investment in Indonesia. The analytical hierarchical process (AHP) technique was used in the quantitative methodology of this study to evaluate the risks faced by insurance companies when investing in infrastructure and to identify strengths and limitations. The results show that insurance funds are a possible alternative funding source for infrastructure projects in Indonesia; as a result, the government provides the necessary instruments, such as important policies and attractive partnership structures and models.